Developing EFL Primary School Teachers’ Storytelling Technique to Support Their Students’ Language Learning in Class at Maitreyawira School Palembang - Sheilla Noveta; Evi Yana (LINGUA: Jurnal Bahasa dan Sastra, 2020)
Abstract: This research aimed to develop EFL primary school teachers’ implementation of storytelling in primary school class. Storytelling has been one of the popular activities held in schools’ competition. However, storytelling is not yet well promoted and implemented within EFL primary school classroom in Palembang. Three EFL teachers were trained on how to develop a lesson plan involving storytelling and given a demonstration on how to conduct storytelling. Four classes were observed for the EFL teachers’ storytelling implementation using storytelling rubric. A questionnaire, an interview and teachers’ reflction were used as other types of measurement. The fidings suggest that EFL teachers still needs help in developing their storytelling technique skills and in implementing storytelling in class. However, the EFL primary school students were very eager in learning English through storytelling activities.Keywords: storytelling, EFL teachers, primary schoolAbstrak: Penelitian ini bertujuan untuk mengembangkan penerapan kegiatan mendongeng pada guru bahasa Inggris di kelas sekolah dasar. Mendongeng menjadi salah satu kegiatan yang populer diadakan pada kompetisi sekolah - sekolah. Namun, kegiatan mendongeng belum dikembangkan dan diterapkan dengan baik di kelas sekolah dasar di Palembang. Tiga guru Bahasa Inggris dilatih bagaimana cara mengembangkan rencana pembelajaran yang melibatkan kegiatan mendongeng dan diberikan demonstrasi bagaimana mendongeng cerita. Empat kelas diobservasi untuk melihat pelaksanaan kegiatan mendongeng guru Bahasa Inggris menggunakan rubrik mendongeng. Kuesioner, wawancara dan reflksi guru digunakan sebagai alat ukur lainnya. Temuan menunjukkan bahwa guru Bahasa Inggris masih membutuhkan bantuan dalam mengembangkan keterampilan teknik mendongeng mereka dan dalam menerapkan kegiatan mendongeng di kelas. Namun, siswa dan siswi sekolah dasar sangat bersemangat dalam belajar bahasa Inggris melalui kegiatan mendongeng.Kata-kata kunci: mendongeng, guru bahasa Inggris, sekolah dasar